Working alliance as a predictor of change in depression during blended cognitive behaviour therapy. Issue 4 (4th July 2019) - Vernmark, Kristofer; Hesser, Hugo; Topooco, Naira; Berger, Thomas; Riper, Heleen; Luuk, Liisa; Backlund, Lisa; Carlbring, Per; Andersson, Gerhard
ABSTRACT: Blended Cognitive Behaviour Therapy (bCBT) is a new form of treatment, mixing internet-based modules and face-to-face therapist sessions. How participants rate the therapeutic alliance in bCBT has not yet been thoroughly explored, and neither is it clear whether therapist- and patient-rated alliances are predictors of change in depression during treatment. Depression and alliance ratings from 73 participants in a treatment study on bCBT (part of the E-COMPARED project) were analysed using growth curve models. Alliance, as rated by both patients and therapists, was high. The therapist-rated working alliance was predictive of subsequent changes in depression scores during treatment, whereas the patient-rated alliance was not. A therapeutic alliance can be established in bCBT. The role of the therapist-rated alliance seems to be of particular importance and should be carefully considered when collecting data in future studies on bCBT.